The Arctic National Wildlife Refuge - Corn, M. Lynne; Kumins, Lawrence C.; Baldwin, Pamela (Library of Congress. Congressional Research Service., 1996)
The Arctic National Wildlife Refuge (ANWR) is an area rich in fauna, flora, and oil potential, where development has been debated for over 36 years. Current law forbids oil and gas leasing. This report discusses debate over whether or not to open the ANWR up for development and includes discussion of various legislative options under consideration.